2019
DOI: 10.1044/2019_jslhr-s-19-0098
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Promotes Phonological Learning in Children Across Language and Autism Spectra

Abstract: Purpose Establishing stable and flexible phonological representations is a key component of language development and one which is thought to vary across children with neurodevelopmental disorders affecting language acquisition. Sleep is understood to support the learning and generalization of new phonological mappings in adults, but this remains to be examined in children. This study therefore explored the time course of phonological learning in childhood and how it varies by structural language an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 87 publications
2
5
0
1
Order By: Relevance
“…The literature indicates that children with language difficulties may have more sleep difficulties (Botting & Baraka, 2018). We have replicated previous research showing increased rates of caregiver reported sleep problems in children with DLD (Botting & Baraka, 2018; Knowland et al., 2021). However, research objectively measuring sleep behaviour in children with DLD has not found worse sleep outcomes or sleep efficiency (Knowland et al., 2021).…”
Section: Discussionsupporting
confidence: 88%
“…The literature indicates that children with language difficulties may have more sleep difficulties (Botting & Baraka, 2018). We have replicated previous research showing increased rates of caregiver reported sleep problems in children with DLD (Botting & Baraka, 2018; Knowland et al., 2021). However, research objectively measuring sleep behaviour in children with DLD has not found worse sleep outcomes or sleep efficiency (Knowland et al., 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Sleep in autism is associated with (1) demographic factors [ 75 77 ], (2) challenging behaviors [ 36 , 78 – 87 ], (3) core ASD symptoms [ 38 , 65 , 77 ], and (4) other psychiatric symptoms [ 84 , 88 , 89 ]. Studies with a developmental focus also document correlations with executive functioning [ 88 , 90 ], memory [ 91 – 93 ], attention [ 79 , 94 ], and phonological learning [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…The This data also adds to the research of how language acquisition is affected by sleep problems in ASD. Few studies focused on this topic and all of them used vocabulary to assess the effect of sleep problems on language (Botting & Baraka, 2018;Fletcher et al, 2020;Knowland et al, 2019). Going forward, one would suggest shifting focus toward receptive and expressive language.…”
Section: Baselinementioning
confidence: 99%
“…Sleep problems have also been reported to affect children’s cognitive development and language acquisition. Multiple studies have shown that improved retention of vocabulary, phonological learning, and language comprehension skills are associated with greater amounts of sleep both in neurotypical children (Axelsson et al, 2016; Henderson et al, 2012) and in children with various developmental disorders (Axelsson et al, 2013; Edgin et al, 2015; Fletcher et al, 2020; Greiner de Magalhães et al, 2020; Knowland et al, 2019). Conversely, it has been shown that children who sleep less have more trouble with consolidation of different elements of memory associated with speech, such as phoneme recognition, vocabulary, and semantic knowledge (Axelsson et al, 2016; Bonuck et al, 2021; Henderson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%